The Rise of Digital Entrepreneurship in Latin America - Andonova, Veneta (2023)
Objective: This article discusses why digital start-ups are flourishing in Latin America. Method: Our research setting is Latin American digital companies. Our analysis is based on digital companies from Brazil, Argentina, Mexico, Chile, and Colombia. We examined lists of Latin unicorn companies (valuation + US$ 1B) and other prominent digital companies compiled from available sources from CB Insights, and TechCrunch. We systematically gathered data on the companies’ growth trajectory from data sources, including online material from the companies’ official websites and public reports, press releases, and press interviews made by the heads of the companies, and internal reports. Main Results: The article discusses the drivers behind the scaling and expansion of digital start-ups and the increasing maturity of the entrepreneurial ecosystems that support them. Relevance / Originality: While Latin digital companies have gained media and investors’ attention, there is scant analysis of how these companies have surpassed the startup stage and scaled up their operations. Theoretical / Methodological Contributions: Our contribution focuses on understanding Latin America’s particular conditions and the impact of digital ventures on the region’s business landscape. We bring practical insights on how Latin American digital companies are growing, as digital entrepreneurship is experiencing an extraordinary growth route in the region and is linked to economic growth and innovation.